Kriteria Patuh Syariah dan Kadar Penghunian Hotel Wakaf - Wan Jusoh, Wan Nur Syakirah; Kasim, Rozilah (Research in Management of Technology and Business, 2020)
The State Islamic Religious Council (MAIN) and Malaysia Waqf Foundation have successfully developed waqf hotels. Among them is the Hotel Klana Beach Resort, Port Dickson which is the selected case hotel of this paper. Waqf horel is a shariah-compliant concept for Islamic hospitality management. Unfortunately, visitors are less interested in waqf hotels due to the hospitality factor of shariah-compliant enforces in the hotel management. Therefore, the objective of this paper is to identify the criteria of shariah-compliance hotels and the relationship with hotel occupancy rate. A quantitative approach was used where descriptive correlational and 35 questionnaires were successfully collected from the 100 forms distributed to the targeted respondents. The correlation involves four independent variables, namely shariah-compliant hotel operations, designs and interior, finance and customers’ attitudes towards the acceptance of shariah-compliant hotel criteria. The results show that the effectiveness of occupancy in the case stuidy hotel is moderate because only the hotel shariah-compliant design and interior scored 0.039 and showed less 0.05 and contributes siognificantly in the correlation. This study can be used as a reference for waqf hotels’ operators in Malaysia.